Fried Chicken's Small Micro-Venture Revenue Increase Strategy Through Digital Media - Lesmana, Teguh; Rohimah, Iim; Selasi, Dini (Journal of International Multidisciplinary Research, 2024)
This study aims to explore the implementation of digital media and sales strategies that contribute to increasing the income of fried chicken MSMEs players in Sedong Village, Sedong District, Cirebon Regency. The research method used is descriptive qualitative, with data collection through observation, interviews, and questionnaires. The respondents of the study consisted of fried chicken MSMEs players in Sedong Village. The results showed that the application of digital media, especially through WhatsApp and Facebook applications, had a positive effect on increasing the income of fried chicken MSMEs players. Sales activities that were originally word-of-mouth developed by utilizing digital media. The use of WhatsApp and Facebook not only expanded the range of product information, but also increased sales volume from 30-50 chickens per day to 70-100 chickens per day. Daily net profit also increased significantly, increasing from Rp. 150,000 - Rp. 200,000 to Rp. 300,000 - Rp. 400,000. Although the application of digital media has a positive impact, MSMEs players have also experienced some negative impacts. Additional expenses to buy data packages or internet quotas are one of the obstacles. In addition, concerns about product imitation by competitors and the presence of fictitious purchases are also felt. The conclusion of this study is that the application of digital media, especially through WhatsApp and Facebook, can be an effective strategy in increasing the income of fried chicken fried chicken MSMEs. However, MSMEs players need to consider negative impacts, such as additional costs and more intensive competition, in utilizing digital media as a sales tool.